JUAL BELI MYSTERY BOX DALAM E-MARKETPLACE DITINJAU DARI PERSPEKTIF HUKUM EKONOMI SYARIAH - Lubis, Ihsan Helmi (Yurisprudentia: Jurnal Hukum Ekonomi, 2024)
The background of this study is related to the practice of buying and selling on e- marketplaces such as Shopee, Tokopedia, Lazada, Blibli, and Bukalapak, which offer products in the form of mystery boxes, i.e., products whose substance, shape, and characteristics are unknown. From the perspective of Islamic law, a valid sale is one that fulfills all the required conditions and terms. The objective of this study is to analyze the practice of selling mystery boxes on e-marketplaces from the perspective of Islamic law, by assessing whether the essential conditions and terms of the sale are met. This research uses a library research method with a case study approach, focusing on several sellers offering mystery box products on e-marketplaces. The research type is descriptive-analytical. The findings of this study show that the practice of selling mystery boxes on e-marketplaces has met the conditions of al-’aqidain (the seller and the buyer) and shighat al-aqd (the declaration of intent of both parties). However, with regard to ma’qud alaih (the object of the sale), the practice contains elements of gharar (uncertainty) and maisir (gambling), due to the lack of clarity regarding the substance, shape, and characteristics of the product to be delivered by the seller to the buyer.